2012
DOI: 10.1007/s10856-012-4773-5
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable poly(lactide-co-glycolide) coatings on magnesium alloys for orthopedic applications

Abstract: Polymeric film coatings were applied by dip coating on two magnesium alloy systems, AZ31 and Mg4Y, in an attempt to slow the degradation of these alloys under in vitro conditions. Poly(lactic-co-glycolic acid) polymer in solution was explored at various concentrations, yielding coatings of varying thicknesses on the alloy substrates. Electrochemical corrosion studies indicate that the coatings initially provide some corrosion protection. Degradation studies showed reduced degradation over 3 days, but beyond th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 28 publications
3
69
0
Order By: Relevance
“…Ostrowaski et al, reported on the corrosion and biocompatibility properties of the PLGA coating of varying thickness on AZ31and MgY4 alloy for orthopaedic applications [93]. In their study, two coatings of different thickness 1.6 μm and 41.8 μm were prepared on AZ31 alloy, whereas 1.6 μm and 62.1 μm thick coatings were deposited on MgY4 alloy.…”
Section: Poly (Lactic-co-glycolic) Acidmentioning
confidence: 99%
“…Ostrowaski et al, reported on the corrosion and biocompatibility properties of the PLGA coating of varying thickness on AZ31and MgY4 alloy for orthopaedic applications [93]. In their study, two coatings of different thickness 1.6 μm and 41.8 μm were prepared on AZ31 alloy, whereas 1.6 μm and 62.1 μm thick coatings were deposited on MgY4 alloy.…”
Section: Poly (Lactic-co-glycolic) Acidmentioning
confidence: 99%
“…3 [40,45]. Figure 4 presents the potentiodynamic polarization curves of the AZ31 substrate, the samples coated with the ZnAl-LDH coating and the LDH/PLA composite coating.…”
Section: Resultsmentioning
confidence: 99%
“…But some of them may release volatile organic compounds during the curing process and results in air pollution. Poly(lactic acid) (PLA) is a natural biocompatible and environment-friendly polymer material made from renewable resources such as corn starch, tapioca roots, chips or starch, or sugarcane [40]. It is worth mentioning that PLA is widely used as medical implants due to their characters of nontoxic, biodegradable and biocompatible [4,[41][42].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the corrosion resistance of the magnesium-based stents in physiological environments, biodegradable polymers such as poly(l-lactic acid) (PLLA), polycaprolactone (PCL), and poly(lactide-co-glycolide) (PLGA) have been widely applied to control the corrosion behavior and maintain surface biocompatibility for the magnesium-based stents [12,13]. However, although providing good protection and enhanced surface biocompatibility for the magnesium substrate, the polymer coatings did not maintain a reduction in corrosion rate over the long term and the inhomogeneous coating durability with gas pocket formation in the polymer coating will result in eventual detachment from the alloy surface [13].…”
Section: Introductionmentioning
confidence: 99%